Real World Experience of Bedaquiline-Based Anti-Tubercular Regime in Multi-Drug Resistant Tuberculosis. - Vikas Marwah; Robin Choudhary; I M Pandey; Sandeep Rana; Anmol Sharma; Srishti Tripathy; Virender Malik; Shrinath V; Jyothis MC; Tentu Ajay (International Journal of Medical Students)
BACKGROUND: Tuberculosis is an important public healthcare problem in our country. Drug-resistant Tuberculosis is like a smoldering fire that if not controlled will flare up to an uncontrolled inferno. The conventional therapy for multidrug-resistant TB is associated with multiple issues like prolonged duration and various side effects. Newer anti-tubercular drugs are available but there is a lack of real-world evidence of their use. Bedaquiline is a novel drug belonging to the dairlyquinolone group. It has a bactericidal action and works by inhibiting the mycobacterial ATP synthase enzyme limiting the provision of ATP to mycobacterium.